Analisis Pertanggungjawaban dan Perlindungan Pidana terhadap Pelaku dan Korban Tindak Pidana Eksibisionisme - Rafadhea Fauzia Aydraghifary; Rinaldy Amrullah; Sri Riski (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines criminal liability for the crime of exhibitionism in Indonesia and the forms of protection provided to its victims. Exhibitionism is a deviant behavior in the form of exposing genitals to others without consent, which is classified as a form of sexual harassment. Although often considered a minor act or even just